2017
DOI: 10.3847/1538-4357/aa62a0
|View full text |Cite
|
Sign up to set email alerts
|

The Greater Taurus–Auriga Ecosystem. I. There is a Distributed Older Population

Abstract: The census of Taurus-Auriga has been assembled over seven decades and inherited the biases and incompleteness of the input studies. The unusual shape of its inferred initial mass function (IMF) and the existence of isolated diskbearing stars suggest that additional (likely disk-free) members remain to be discovered. We therefore have begun a global reassessment of the census of Taurus-Auriga that exploits new data and better definitions of youth and kinematic membership. As a first step, we reconsider the memb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
158
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(175 citation statements)
references
References 158 publications
(301 reference statements)
16
158
0
Order By: Relevance
“…We also reject a few stars from the latter that do not appear to be members. Kraus et al (2017) Kraus et al (2017) compiled diagnostics of membership in the Taurus star-forming region for 396 candidate members that had been identified in previous surveys. They selected candidates that lacked evidence of disks in earlier studies 4 and that were within a large area extending well beyond the Taurus clouds that was defined by right ascensions (α) of 3 h 50 m -5 h 40 m and declinations (δ) of 14…”
Section: Previously Known Members Of Taurusmentioning
confidence: 99%
See 3 more Smart Citations
“…We also reject a few stars from the latter that do not appear to be members. Kraus et al (2017) Kraus et al (2017) compiled diagnostics of membership in the Taurus star-forming region for 396 candidate members that had been identified in previous surveys. They selected candidates that lacked evidence of disks in earlier studies 4 and that were within a large area extending well beyond the Taurus clouds that was defined by right ascensions (α) of 3 h 50 m -5 h 40 m and declinations (δ) of 14…”
Section: Previously Known Members Of Taurusmentioning
confidence: 99%
“…Some candidates lacked sufficient data for definitive assessments of their membership. Kraus et al (2017) concluded that 218 of the 396 candidates were confirmed or likely members, 82 of which were absent from the compilation of members in Luhman et al (2017). Most of those 82 stars are older (10-30 Myr) and more widely distributed than the previously known members (∼ 1 Myr), so Kraus et al (2017) proposed that they represent an earlier generation of star formation that is related to the Taurus cloud complex.…”
Section: Candidate Members Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Together with several other targets of the same survey, HD 284149 has been proposed to be part of the so-called Taurus-Ext association (Luhman et al 2017;Kraus et al 2017;Daemgen et al 2015), a group of stars with similar space position and kinematics of the Taurus star forming region but distinctly older ages. A dedicated age estimate was then performed for HD 284149 by Bonavita et al (2014), using several youth indicators, leading to an adopted age of 25 +25 −10 Myrs.…”
Section: Introductionmentioning
confidence: 99%